Frontiers in Algorithmics : 9th International Workshop, FAW 2015, Guilin, China, July 3-5, 2015, Proceedings - Wang, Jianxin; Yap, Chee.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 9th International Workshop on Frontiers in Algorithmics, FAW 2015, held in Guilin, China, in July 2015. The 28 papers presented in this volume were carefully reviewed and selected from 65 submissions. They deal with graph algorithms, approximation algorithms, combinatorial optimization, parameterized algorithms, and online algorithms.
Graph Modification Problems: A Modern Perspective -- Soft Subdivision Search in Motion Planning, II: Axiomatics -- On r-Gatherings on the Line -- A New Algorithm for Intermediate Dataset Storage in a Cloud-Based Dataflow -- Efficient Computation of the Characteristic Polynomial of a Threshold Graph -- A Fast and Practical Method to Estimate Volumes of Convex Polytopes -- Social Models and Algorithms for Optimization of Contact Immunity of Oral Polio Vaccine -- The Directed Dominating Set Problem: Generalized Leaf Removal and Belief Propagation -- A Linear Time Algorithm for Ordered Partition -- Machine Scheduling with a Maintenance Interval and Job Delivery Coordination -- Lower and Upper Bounds for Random Mimimum Satisfiability Problem -- On Solving Systems of Diagonal Polynomial Equations Over Finite Fields -- Pattern Backtracking Algorithm for the Workflow Satisfiability Problem with User-Independent Constraints -- On the Sound Covering Cycle Problem in Paired de Bruijn Graphs -- Approximation Algorithms for the Multilevel Facility Location Problem with Linear/Submodular Penalties -- Smaller Kernels for Several FPT Problems Based on Simple Observations -- ParameterizedMinimum Cost Partition of a Tree with Supply and Demand -- The Online Storage Strategy for Automated Storage and Retrieval System with Single Open in One Dimension -- Union Closed Tree Convex Sets -- Fast Quantum Algorithms for Least Squares Regression and Statistic Leverage Scores -- A New Distributed Algorithm for Computing a Dominating Set on Grids -- Approximate Model Counting via Extension Rule -- Improved Information Set Decoding for Code-Based Cryptosystems with Constrained Memory -- Truthful Strategy and Resource Integration for Multi-tenant Data Center Demand Response -- Local Search to Approximate Max NAE-k-Sat Tightly -- Faster Computation of the Maximum Dissociation Set and Minimum 3-Path Vertex Cover in Graphs -- Enumeration, Counting, and Random Generation of Ladder Lotteries -- Efficient Modular Reduction Algorithm Without Correction Phase -- Super Solutions of Random Instances of Satisfiability -- A Data Streams Analysis Strategy Based on Hadoop Scheduling Optimization for Smart Grid Application.
Keywords: Computer software; Computational complexity; Computer science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Computation by Abstract Devices